Brown trout (Salmo trutta L.) high genetic diversity around the Tyrrhenian Sea as revealed by nuclear and mitochondrial markers - P. Berrebi; V. Caputo Barucchi; A. Splendiani; S. Muracciole; A. Sabatini; F. Palmas; C. Tougard; M. Arculeo; S. Marić (Hydrobiologia, 2019)

Museum samples could help to reconstruct the original distribution of Salmo trutta complex in Italy - A. Splendiani; T. Fioravanti; M. Giovannotti; L. Olivieri; P. Ruggeri; P. Nisi Cerioni; S. Vanni; F. Enrichetti; V. Caputo Barucchi (Journal of Fish Biology, 2017)
Partial D‐loop sequences of museum specimens of brown trout and marble trout ( Salmo trutta species complex ) collected from Mediterranean rivers in the late 19th century were analysed to help to describe the native distribution of these species. All the individuals studied carried native haplotypes, the geographic distribution of which is consistent with published data. These results indicate that museum specimens from the 19th century could represent an opportunity to get a picture of the original genetic diversity distribution of this species complex.

Evolutionary dynamics of Anolis sex chromosomes revealed by sequencing of flow sorting-derived microchromosome-specific DNA - Ilya G. Kichigin; Massimo Giovannotti; Alex I. Makunin; Bee L. Ng; Marsel R. Kabilov; Alexey E. Tupikin; Vincenzo Caputo Barucchi; Andrea Splendiani; Paolo Ruggeri; Willem Rens; Patricia C. M. O’Brien; Malcolm A. Ferguson-Smith; et al. (Molecular Genetics and Genomics, 2016)

Alien brown trout invasion of the Italian peninsula: the role of geological, climate and anthropogenic factors - A. Splendiani; P. Ruggeri; M. Giovannotti; S. Pesaresi; G. Occhipinti; T. Fioravanti; M. Lorenzoni; P. Nisi Cerioni; V. Caputo Barucchi (Biological Invasions, 2016)

Isolation and characterisation of novel microsatellite loci in the transparent goby Aphia minuta (Perciformes, Gobiidae) - P. Ruggeri; A. Splendiani; M. Giovannotti; T. Fioravanti; P. Nisi Cerioni; V. Caputo (Conservation Genetics Resources, 2013)

Isolation of novel microsatellite loci in the black goby Gobius niger and cross‐amplification in other gobiid species (Perciformes, Gobiidae) - P. Ruggeri; A. Splendiani; M. Giovannotti; P. Nisi Cerioni; V. Caputo (Journal of Fish Biology, 2012)
Twelve microsatellite loci were isolated from and characterized for the black goby Gobius niger . These loci were tested on a total of 48 individuals from two geographically distant locations (Orbetello and Cattolica) and the number of alleles ranged from two to 18, with expected ( H e ) and observed ( H o ) heterozygosities ranging from 0·042 to 0·941 and from 0·042 to 0·917, respectively. The loci described were used to cross‐amplify other gobiid species belonging to Gobius , Zosterisessor , Lesueurigobius and Aphia .

Mitochondrial DNA variation of an isolated population of the Adriatic brook lamprey Lampetra zanandreai (Agnatha: Petromyzontidae): phylogeographic and phylogenetic inferences - V. Caputo; M. Giovannotti; P. Nisi Cerioni; A. Splendiani; M. Marconi; J. Tagliavini (Journal of Fish Biology, 2009)
Two mitochondrial genes were examined to compare an isolated population of the Adriatic brook lamprey Lampetra zanandreai in central Italy with other populations in the species range (Po plain) and with parasitic and freshwater lampreys. A single haplotype, identical to one in a Venetian sample, was found in 10 individuals from the isolated population. The reduced variability is consistent with a history of dispersal after the Pleistocene expansion of the Po basin. The results support the hypothesis of an origin of L. zanandreai and L. fluviatilis – L. planeri from a common anadromous ancestor.

Genetic diversity of brown trout in central Italy - V. Caputo; M. Giovannotti; P. Nisi Cerioni; M. L. Caniglia; A. Splendiani (Journal of Fish Biology, 2004)
Genetic diversity was analysed in brown trout Salmo trutta populations living in an area of central Italy using RFLP analysis of two mtDNA segments and of the nuclear locus LDH‐C1 *. The data indicated a genetic structure profoundly altered by repeated stockings with allochthonous material of Atlantic origin. In fact, four and 11 of the haplotypes detected were, respectively, identical or genetically very close to haplotypes found in Danish populations, the putative source of stocked brown trout. Furthermore, the LDH‐C1 * 90 allele, typical of north‐western Europe, was widespread among the samples studied. Nonetheless, four populations are characterized by a high frequency of both putative autochthonous haplotypes and the LDH‐C1 * 100 allele, common in the Mediterranean basin. These populations, sampled in areas where S. trutta is documented historically, might represent a remnant of the species’ indigenous biodiversity, showing the scope for improving the management of brown trout in central Italy.